Targeting the NFAT1-MDM2-MDMX Network Inhibits the Proliferation and Invasion of Prostate Cancer Cells, Independent of p53 and Androgen - Qin, Jiang-Jiang; Li, Xin; Wang, Wei; Zi, Xiaolin; Zhang, Ruiwen (Frontiers in Pharmacology, 2017)
The MDM2 and MDMX oncogenes are overexpressed in various types of human cancer and are highly associated with the initiation, progression, metastasis and chemotherapeutic resistance of these diseases, including prostate cancer. The present study was designed to test a natural MDM2 inhibitor, Inulanolide A (InuA), for anti-prostate cancer activity and to determine the underlying mechanism(s) of action. InuA directly bound to the RING domains of both MDM2 and MDMX with high affinity and specificity and disrupted MDM2-MDMX binding, markedly enhancing MDM2 protein degradation. We further discovered that InuA bound to the DNA binding domain of NFAT1, resulting in marked inhibition of MDM2 transcription. InuA inhibited the proliferation, migration, and invasion of prostate cancer cells, regardless of their p53 status and AR responsiveness. Double knockdown of MDM2 and NFAT1 also revealed that the expression of both of these molecules is important for InuA’s inhibitory effects on the proliferation and invasion of prostate cancer cells. In summary, InuA represents a novel class of bifunctional MDM2 inhibitors, and should be further investigated as a candidate lead compound for prostate cancer prevention and therapy.